Ore Handling for the McArthur River and Cigar Lake Projects - Chuck Edwards (Canadian Institute of Mining, Metallurgy and Petroleum, 1997)
"The development of two large, high-grade uranium projects has been proposed for northern Saskatchewan. The projects are now under review by a joint federal/provincial panel. The McArthur River project is owned by the McArthur River joint venture (Cameco Corporation 53.991 %, Uranerz Exploration and Mining Limited 29.775%, Cogema Resources Inc. 16.234%) and operated by Cameco. Cameco proposes to mill the McArthur River ore at the existing Key Lake mill. The Cigar Lake project is owned by the Cigar Lake joint venture (Cameco Corporation 48.75%, Cogema Resources Inc. 36.375%, Idemitsu Uranium Exploration Canada Ltd. 12.875%, Korea Electric Power Corporation 2.000%). The Cigar Lake joint venture proposes that Cameco operate the Cigar Lake mine for the owners, and that Cogema mill the ore at their McClean Lake mill, now under construction. Proposed systems provide safe mining and ore handling, and allow the milling of McArthur River ore at Key Lake and Cigar Lake ore at McClean Lake. This avoids the disturbance of new sites for milling and tailings disposal.The McArthur River and Cigar Lake deposits are the largest known high-grade uranium deposits in the world. The ore grades at McArthur River and Cigar Lake are at least 100 times those that are mined elsewhere. It is proposed to mine these deposits using remote underground mining methods, to crush and grind the ore underground, to pump a thickened ore slurry to surface, and to transport it in special containers by truck to the mills.During all mining and processing stages the ore is fully contained. Radon emission is controlled by positive ventilation of all process vessels, with the process ventilation backed up by the primary mine ventilation system. Radiation is controlled by heavy steel pipe and vessel walls, concrete walls and sometimes lead sheeting."